Student Debt and Access to Higher Education in Chile [Endeudamiento Estudiantil y Acceso a la Educación Superior en Chile] - Olavarria-Gambi, M (2013)
This paper analyses whether the fear of indebtedness resulting from going on to post-secondary education affects potential students decisions to apply for, and enter into, Higher Education; whether there is any relationship between the fear of indebtedness and the socio-economic level of the families of potential students; and whether there is an association between the fear of indebtedness and student performance. This study shows that the fear of indebtedness for post-secondary studies is not a limiting factor for young people from lower-income sectors to go on to tertiary education. The study also shows that availability of loans facilitates access to Higher Education. These findings contradict the conclusions of studies by Claire Callender and Jonathan Jackson, who previously analysed the British case with the same aims.